Kesiapan Masyarakat Dalam Pengelolaan Hutan Berbasis Agoforestri Kemiri - Dienul Aslam; Golar Golar; Zulkaidah Zulkaidah (Mitra Sains, 2020)
Candlenut agroforestry is the priority land management belongs to the Palolo community, especially in Sigimpu Village and Bakubakulu Village, Sigi Regency. The communities give more and more their attention because the monoculture has showed vulnerability to climate change and global warming. Adopting candlenut agroforestry in land management could be optimized under condition of good community readiness supporting the management system. This study aimed to measure the level of community readiness in the management of candlenut agroforestry in the villages and compare the level of readiness. Community Readiness Model (CRM) is used by taking into account six dimensions and nine levels of readiness. In between of two components, 35 questions based on the dimensions were made. Three respondents were selected representing each community group in the villages by which has four community group each. The results of the CRM analysis show that the level of community readiness is at the initiation level for Sigimpu Village with a value of 6.1 while the level of preparation for Bakubakulu Village is 5.9. In candlenut agroforestry-based forest management in Sigimpu and Bakubakulu Villages there are differences in two dimensions, namely community knowledge with 6,5 and 6,0 of readiness values and resource dimension with 5,8 and 5,2 of values. Thus, the level of community readiness in the study area is in the intermediate level.